3-Week passive acclimation to extreme environmental heat (100± 3 °C) in dry sauna increases physical and physiological performance among young semi-professional football players. (August 2021) - Bartolomé, I.; Siquier-Coll, J.; Pérez-Quintero, M.; Robles-Gil, M.C.; Grijota, F.J.; Muñoz, D.; Maynar-Mariño, M.
Abstract: This manuscript aims to evaluate the influence of a novel passive heat acclimation program among human participants in the physical performance, as well as in several physiological parameters. 36 male football players were acclimated using a dry sauna bath to extreme hot (100 ± 3 °C), performing a total of nine sauna sessions with a weekly frequency of three sessions. The players were randomly into the sauna group (SG; n = 18; age: 20.69 ± 2.09 years) and the control group (CG; n = 18; age: 20.23 ± 1.98 years). All participants performed maximal effort test until exhaustion as well as hamstring flexibility test before and after the acclimation program. Anthropometric, respiratory, circulatory, hematological and physiological variables were evaluated at the beginning and at the end of the survey. Statistical analysis consisted of a Mann-Whitney U test to determine differences between groups at the beginning and at the end of the survey and a Wilcoxon test for paired samples to compare the differences for each group separately. Additionally, size effects of the pre-post acclimation changes were calculated. After the acclimation program SG participants experienced a diminution in body weight (p < 0.01), body mass index (p < 0.01), body fat (p < 0.05) and fat percentage (p < 0.05) decreased. Hamstring flexibility (p < 0.05) and work capacity (p < 0.05) increased. External basal temperature decreased (p < 0.05) as well as post-exercise systolic and diastolic blood pressures (p < 0.05). Finally, maximal oxygen uptake (ml Kg −1 min −1 ) (p < 0.05), maximal minute ventilation (p < 0.05) and maximal breath frequency (p < 0.05) increased at the end of the intervention. There were no significant changes in the CG in any variable. Favorable adaptations have been observed in this survey, suggesting a beneficial effect of extreme heat acclimation on physical performance. Several of the observed responses seem interesting for sport performance and health promotion as well. However, this is a novel, extreme protocol which requires further research. Highlights: Passive acclimation to extreme heat (100 °C) has been proved for the first time to increase maximal effort capacity in young sportsmen accompanied by an increase in absolute VO2max and in several cardiorespiratory parameters. The increase in the physical performance were accompanied by an enhancement in body composition without modifications in body weight. Percentage and absolute lean mass increased while percentage and absolute fat mass decreased. These adaptions were not observed among sportsmen of similar characteristics who did not perform the exposure program to heat and who performed the same training routine. A total exposure time to heat of 2 h were applied during three consecutive weeks. The exposure system consisted of three weekly sessions of interval exposures of 40 min